PENGARUH BIMBINGAN KELOMPOK TERHADAP PENINGKATAN EMPATI SISWA DI KELAS X MIPA 3 SMA NEGERI 12 PEKANBARU TAHUN AJARAN 2015/2016 - Maryati Puteri Septami; Tri Umari; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of the increase in emaptistudents in the experimental group. The research method Control Group pre-test-posttest.Subjek in this study were 22 students who have low empathy in class X SMA Negeri12 Pekanbaru.Hasil MIPA research is to test different before and after the implementationof group counseling in the experimental group using the program SPSS formula obtainedresults Wilcoxon Z = -3125 with sig. (2-tailed) of 0002, because sig. (2-tailed) <0.05 then